2014
DOI: 10.3109/10717544.2014.889779
|View full text |Cite|
|
Sign up to set email alerts
|

Bumadizone calcium dihydrate microspheres compressed tablets for colon targeting: formulation, optimization andin vivoevaluation in rabbits

Abstract: The objective of this study was the development of a colon-targeted microspheres which were compressed into tablets containing the non-steroidal anti-inflammatory bumadizone calcium dihydrate. A 3 2 full factorial design was adopted for the evaluation of the prepared microspheres. The effect of two independent variables namely polymer type (Eudragit RS100, ethyl cellulose and cellulose acetate butyrate), and drug: polymer ratio (1:1, 9:1 and 18:1) was studied on the entrapment efficiency and in vitro drug rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In 2015, Nour and colleagues formulated an optimized microspheres in compressed tablet of bumadizone calcium dihydrate for colon targeting and controlled release. Their findings showed that microspheres based on ethylcellulose N100 displayed the highest entrapment efficiency which was attributed to its higher viscosity and ability to decrease drug diffusion to the outer phase increasing retention within the microsphere core as well as extended in vitro and in vivo release behaviour (Nour et al, 2015). The drug release retarding properties of ethylcellulose also found application in the construction of a once-daily dosing sustained release coated tablet of tolterodine-L-tartrate in the management of overactive bladder.…”
Section: Macro-structured Delivery Systems Fabricated From Ethylcellumentioning
confidence: 99%
“…In 2015, Nour and colleagues formulated an optimized microspheres in compressed tablet of bumadizone calcium dihydrate for colon targeting and controlled release. Their findings showed that microspheres based on ethylcellulose N100 displayed the highest entrapment efficiency which was attributed to its higher viscosity and ability to decrease drug diffusion to the outer phase increasing retention within the microsphere core as well as extended in vitro and in vivo release behaviour (Nour et al, 2015). The drug release retarding properties of ethylcellulose also found application in the construction of a once-daily dosing sustained release coated tablet of tolterodine-L-tartrate in the management of overactive bladder.…”
Section: Macro-structured Delivery Systems Fabricated From Ethylcellumentioning
confidence: 99%
“…PS and ZP were not taken into consideration as the results showed statistical insignificant differences (Nour et al, 2015). The highest desirability value obtained was 0.921 and it was associated with the independent variables, namely, X 1 ¼ 50%, X 2 ¼ 40, and X 3 ¼ 10 corresponding to formula PM7.…”
Section: Selection Of the Optimized Pm Formulamentioning
confidence: 99%
“…In the FDA ‘Inactive Ingredient Database’ and the United States Pharmacopeia, CAB is listed as ‘Cellaburate’ [ 17 , 18 ]. The literature has reported its application in fabrication of various drug delivery systems, e.g., nanoparticles [ 19 ], microspheres [ 20 , 21 ], colonic system [ 22 , 23 ], matrix tablets [ 24 ], gastroretentive [ 25 ], osmotic [ 26 ], and so on. It can also be used as a coating polymer for sustained/extended release of drugs.…”
Section: Introductionmentioning
confidence: 99%